Administrative Governance to Increase the Quality of Administrative Services in PT. BAM REGENCY Tegal - Aria Mulyapradana; Atik Indah Lazulfa (Politeknik Ganesha Medan, 2018)
This study aims to find out the implementation of administrative governance to improve service quality at PT. BAM. Measurements use principles in administering administrative governance (principles of planning, simplifying principles, savings principles, removal principles and merger principles) and reference measures of service quality (tangibles, reliability, responsiveness, assurance, empathy). The main question in this study is how the principles in running administrative governance in PT. BAM Kabupaten Tegal. The results of this study found some things that must be improved in order to improve the quality of administrative services ie administrative governance in PT. BAM on the principle of planning and simplification that needs to improve on indicators tangibles, reliability and responsiveness. The improvement and standardization of operational procedures of SOPs will have an impact on improving the quality of services provided and running periodic employee performance evaluations.